2018
DOI: 10.3139/120.111148
|View full text |Cite
|
Sign up to set email alerts
|

Combined impact of UV radiation and nitric acid on HDPE containers during outdoor exposure

Abstract: Unpigmented HDPE jerrycans filled with nitric acid (55 wt.-%) and water respectively had been exposed to outdoor conditions for one Berlin summer season. As both liquids underwent equal temperature progression, exposure effects of UV radiation and nitric acid as well as of the combination of both can be separated and compared. On the basis of various property changes after these exposures, synergistic action is evaluated and compared to a damaged Intermediate Bulk Container (IBC) from a transport accident. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 44 publications
1
9
1
Order By: Relevance
“…2). This behavior is possibly due to the embrittlement of PE induced by acidic conditions, regardless of the surface oxidation (Geburtig et al 2018). Acidic conditions, in fact, are also observed to negatively affect the tensile strength of PE films (Wang et al 2021).…”
Section: Physicochemical Ageing: the Effects Of Water Chemistrymentioning
confidence: 99%
“…2). This behavior is possibly due to the embrittlement of PE induced by acidic conditions, regardless of the surface oxidation (Geburtig et al 2018). Acidic conditions, in fact, are also observed to negatively affect the tensile strength of PE films (Wang et al 2021).…”
Section: Physicochemical Ageing: the Effects Of Water Chemistrymentioning
confidence: 99%
“…1.6 e, it can be used as a standard liquid for verifying the chemical compatibility testing of polyethylene packaging, for all substances having an oxidizing effect on PE. However, it was shown 2 for several transparent HDPE jerrycans that a simple storage of the 55% nitric acid (HNO 3 -55%) does not necessarily lead to oxidation. Instead, it was found that the UV radiation transmitted through the HDPE can decompose the filling good 3 and then the resulting decomposition products damage the HDPE (secondary damage).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen dioxide NO 2 is a free radical that can act as an autoxidation initiator 4 in HDPE, leading to strong oxidation of the polyethylene (PE) molecules through the formation of carbonyl groups. 5 Outdoor exposures, as in Geburtig et al, 2 have a bad reproducibility as well as several safety challenges. Especially because of the strong temporal variability of the weather, they are not suited for extensive systematic further investigations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations